2023
DOI: 10.1186/s12974-023-02829-3
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone attenuates Th17-cell pathogenicity in autoimmune uveitis via Id2/Pim1 axis

Abstract: Background Autoimmune uveitis (AU) is the most common ophthalmic autoimmune disease (AD) and is characterized by a complex etiology, high morbidity, and high rate of blindness. AU remission has been observed in pregnant female patients. However, the effects of progesterone (PRG), a critical hormone for reproduction, on the treatment of AU and the regulatory mechanisms remain unclear. Methods To this end, we established experimental autoimmune uveit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Research focusing on endotoxin-induced uveitis (EIU) has revealed that suppression of the AP-1 signaling pathway leads to the inhibition of EIU ( 63 65 ). In EAU, downregulation of the AP-1 signaling pathway in Th17 cells and Treg cells has been observed in a study of EAU ameliorated by progesterone ( 66 ). However, AP-1 is an upstream transcription factor activated by diverse growth factors and inflammatory cytokines, and has been implicated in T cell responses.…”
Section: Discussionmentioning
confidence: 96%
“…Research focusing on endotoxin-induced uveitis (EIU) has revealed that suppression of the AP-1 signaling pathway leads to the inhibition of EIU ( 63 65 ). In EAU, downregulation of the AP-1 signaling pathway in Th17 cells and Treg cells has been observed in a study of EAU ameliorated by progesterone ( 66 ). However, AP-1 is an upstream transcription factor activated by diverse growth factors and inflammatory cytokines, and has been implicated in T cell responses.…”
Section: Discussionmentioning
confidence: 96%